Comparison of practical methods for an efficient FPGA implementation of STAP. Issue 9 (2nd September 2019) - Hasanikhah, Narjes; Amin-Nejad, Siavash; Darvish, Ghafar; Moniri, M. R.
ABSTRACT: This study investigated and compared the practical methods used for the efficient Field- Programmable Gate Array (FPGA) implementation of space-time adaptive processing (STAP). The most important part of calculating the STAP weights is the QR decomposition (QRD), which can be implemented using the modified Gram-Schmidt (MGS) algorithm. The results show that the method that uses QRD with less computational burden leads to a more effective implementation. Its structure was parameterised with the vector size to create a trade-off between the hardware and performance factors. For this purpose, QRD-MGS algorithm was first modified to increase the speed, and then the STAP weight vector was calculated. The implementation results show that decreasing the vector size decreases the resource utilisation, computational burden and the consumption power. While the computation time increases slightly, the updated rate of the STAP weights is maintained. For example, the STAP weights in a system with 6 antenna arrays, 10 received pulses and 200 range samples computed in 262 µs using a vector size of 17 on the Arria10 FPGA that has a maximum of 155 µs correlates to the QRD-MGS algorithm and 107 µs correlates to the other parts. Therefore, QRD-MGS algorithm is the most important component of the calculation of the STAP weight vector, and its simplification leads to efficient implementation.